FINANCIAL DEREGULATION AND GLOBAL ECONOMIC CRISIS - Flores Konja, Adrián Alejandro (2011)
This article examines the changes in rules and practices in the financial sector globally, and it is related to the financial crisis of 2007 U.S. and European economic crisis. We leave the analysis of the Report of the Federal Commission of Inquiry into the Financial Crisis of the United States, January 2011.Trataremos to establish a preliminary relationship between changes in rules, practices and policies established classic since 1933 in the United States - and subsequent events. In particular, it seeks to link the financial deregulation policies imposed from 1971, to the original Bretton Woods Agreement of 1944, the international monetary and financial order, especially the repeal of the Banking Act 1999 - legislation Glass - Steagall - that separated the financial sector linked to the production and physical distribution, speculative financial sector, which provided also a security and protection to the former and the latter severe regulations. Since then, speculation began to displace the financial activities related to the real sector, as evidenced by the growth of financial derivatives. At present, the U.S. financial crisis has made European (Portugal, Ireland, Greece and Spain) and is actually a conglomerate banking crisis internationalized, and this complicated state finances with a huge debt to save the speculative financial system with the rejection of populations, the political crisis and the consequent increased risk.